A Political Science Manifesto for the Age of Populism Challenging Growth, Markets, Inequality and Resentment - Ricci, David M. (Social Sciences, 2020)
Modern capitalism, via creative destruction, produces economic winners and losers. The US needs political thought focused not only on efficiency, but also community. If creativity continues - as with driverless cars and 3-D printing - its social effects must be mitigated to avoid electoral backlashes into the undemocratic politics of populism. This title is also available as Open Access on Cambridge Core.